'We are not going to shut down, because we cannot postpone pregnancy': a mixed-methods study of the provision of maternal healthcare in six referral maternity wards in four sub-Saharan African countries during the COVID-19 pandemic. Issue 2 (10th February 2022) - Semaan, Aline; Banke-Thomas, Aduragbemi; Amongin, Dinah; Babah, Ochuwa; Dioubate, Nafissatou; Kikula, Amani; Nakubulwa, Sarah; Ogein, Olubunmi; Adroma, Moses; Anzo Adiga, William; Diallo, Abdourahmane; Diallo, Lamine; et al.
Abstract : Introduction: Referral hospitals in sub-Saharan Africa are located in crowded urban areas, which were often epicentres of the COVID-19 pandemic. This paper prospectively assesses how maternal healthcare was provided in six referral hospitals in Guinea, Nigeria, Tanzania and Uganda during the first year of the COVID-19 pandemic. Methods: Mixed-methods design using three data sources: (1) qualitative data from repeated rounds of semi-structured interviews conducted between July 2020 and February 2021 with 22 maternity skilled heath personnel (SHP) on perceptions of care provision; (2) quantitative monthly routine data on caesarean section and labour induction from March 2019 to February 2021; and (3) timeline data of COVID-19 epidemiology, national and hospital-level events. Qualitative and quantitative data were analysed separately, framed based on timeline analysis, and triangulated during reporting. Results: We identified three periods: first wave, slow period and second wave. The first wave was challenging for SHP given little knowledge about COVID-19, lack of infection prevention and control training, and difficulties reaching workplace. Challenges that persisted beyond the first wave were shortage of personal protective equipment and no rapid testing for women suspected with COVID-19. We noted no change in the proportion of caesarean sections during the pandemic, and a small increase in the proportion of labour inductions. All hospitals arranged isolation areas for women suspected/confirmed with COVID-19 and three hospitals provided care to women with suspected/confirmed COVID-19. Breastfeeding was not discouraged and newborns were not separated from mothers confirmed with COVID-19. Care provision was maintained through dedication of SHP, support from hospital management and remote communication between SHP. Conclusion: Routine maternal care provision was maintained in referral hospitals, despite first wave challenges. Referral hospitals and SHP contributed to guideline development for pregnant women suspected/confirmed with COVID-19. Maternity SHP, women and pregnancy must always be included in priority setting when responding to health system shocks, including outbreaks.